School as a space for nursing: a review of health literacy - Sousa, Paulo Henrique Leal de; Alencar , Nadyelle Elias Santos; Gouveia, Marcia Teles de Oliveira (Revista de Enfermagem da UFPI, 2024)
Objective: To understand the role of school nursing in the context of child and adolescent health literacy. Methods: An integrative review using the Web of Science, MEDLINE/Pubmed, Scopus, Cinahl, Virtual Health Library databases, and search terms related to child and adolescent health, health literacy, and school nursing. No time or language limits were considered. Results: 419 articles were identified and, after excluding duplicates and applying the eligibility criteria, seven articles made up the final sample, none of them developed in Brazil. Despite being a field of research that is still little studied, the results revealed the positive impact of nursing in the school context in promoting physical and mental health literacy, preventing preventable illnesses, and managing chronic non-communicable diseases. This evidence leads to reflections on the recognition of school nursing in Brazil. Conclusion: Nurses are references in the implementation of health literacy programs and in the construction of health literate organizations. In the Brazilian context, there is an urgent need to expand the training of nurses trained to work in schools.